Mechanical Characteristics Of Composite Materials Made From Polyester Resin Mixed With Cocopeat On Static Loads - Balkhaya, Balkhaya; Sufyanto; Fitriadi, Nuzuli; Yusrizal (LPPM Politeknik Aceh Selatan, 2024)
Cocopeat is a binder between coconut fibers in coconut fiber. Cocopeat has high lignin and cellulose content and is resistant to bacteria and fungi. The aim of the research was to determine the mechanical characteristics of cocopeat mixtures with various dosage ratios of 20%, 40%, 60% to 80%. Mechanical characteristic testing is carried out by applying a load to specimens that have been made in accordance with ASTM D 638-03 standards. The maximum load given is 980N. The test results show that the highest stress value is found in the 40% cocopeat mixture composition, which is 8.1902 Mpa and the highest elastic modulus is found in the 20% cocopeat mixture composition, which is 13.8x10-3 Gpa, while the lowest tensile stress value is found in the 60% cocopeat mixture. and the lowest modulus of elasticity was found in a composition of 80% cocopeat mixture, namely 5.12 x 10-4 Gpa. Thus, more and more cocopeat powder is added to composite materials made from polyester resin. This causes a decrease in the value of stress and modulus of elasticity.